Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4236/ojrm.2012.13008
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage phenotypes correspond with remodeling outcomes of various acellular dermal matrices

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 25 publications
(32 reference statements)
1
32
0
Order By: Relevance
“…The ratio of MR+ (M2-marker (Agrawal, 2012;Mantovani, 2006;Choi et al, 2010)) cells to Calprotectin+ (M1-marker (Bartneck et al, 2010)) cells was ∼3 on PS and decreased to ∼1 on O 2 -PS40 (Fig. 2).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The ratio of MR+ (M2-marker (Agrawal, 2012;Mantovani, 2006;Choi et al, 2010)) cells to Calprotectin+ (M1-marker (Bartneck et al, 2010)) cells was ∼3 on PS and decreased to ∼1 on O 2 -PS40 (Fig. 2).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, M2 macrophages secrete large amounts of anti-inflammatory and pro-fibrotic cytokines such as IL-10 (Mantovani, 2006), transforming growth factor (TGF-␤) (Hao et al, 2012), and IL-1 receptor antagonist (IL-1RA) (Baitsch et al, 2011). In addition, these cells express high levels of mannose receptor (MR) (Agrawal, 2012;Mantovani, 2006;Choi et al, 2010) and the scavenger receptor CD163 (Edin et al, 2012;Mantovani, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, macrophages predictably increased or decreased gene expression of known markers of macrophage phenotype when the environmental stimuli were switched, but expression and secretion of the angiogenic proteins VEGF and PDGF were less predictable. Further research is required to investigate the role of these hybrid phenotypes in regulating angiogenesis, especially considering that “mixed” phenotypes have been associated with blood vessel development and scaffold vascularization [20, 21, 52]. Another interesting result was that M2 macrophages proliferated in vitro , which was recently described in vivo as a normal response to IL4 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that both functionally active populations of pro- and anti-inflammatory cells (e.g., M1 and M2 macrophage phenotypes) are important for de novo regeneration of VML injured skeletal muscle. In support of this speculation, other studies have also demonstrated that coordinated efforts by both M1 and M2 macrophage phenotypes are necessary for scaffold vascularization [42] and remodeling [43] . A recent study by Novak et al ., reported that macrophage populations present after muscle laceration injury, did not conform to the canonical M1/M2 classification.…”
mentioning
confidence: 83%